Lingual thyroid: a report of three cases and literature review - Ferreira Gapo, Carla (2008)
Introduction: the term “lingual thyroid” is applied to a mass of ectopic thyroid tissue located at the tongue base in the midline. It is believed to be the result of failure of the embryonic gland anlage to descend from its original position to its normal cervical location early in the course of embryogenesis. Most often asymptomatic, dysphagia, dysphonia, dyspnoea or haemorrhage can be present.Material and methods: Three cases diagnosed and managed at our department from 2000 to 2006 and literature review on the subject.Results: in our series all patients were female, functionally hypothyroid, with a complete absence of pre-tracheal thyroid tissue. Surgical removal was reserved for severely symptomatic cases of dysphagia or airway obstruction (n=1) and haemorrhage (n=1).Conclusions: Lingual thyroid is a rare clinical entity potentially underdiagnosed. It should always be considered in differential diagnosis of midline masses within the tongue base.